Prehistoric textiles : the development of cloth in the Neolithic and Bronze Ages with special reference to the Aegean - Barber, E. J. W., 1940- (Princeton University Press, 1992)
Using innovative linguistic techniques, along with methods from palaeobiology and other fields, this book shows that spinning and pattern weaving began far earlier than has been supposed. Cloth making was an industry that consumed more time and effort, and was more culturally significant to prehistoric cultures, than anyone previously assumed. The textile industry is in fact older than pottery, and perhaps even older than agriculture and stockbreeding.